A CRITICAL ASSESSMENT OF CLASSICAL AND SEMI-CLASSICAL MODELS FOR ELECTRON TRANSFER REACTIONS IN SOLUTION. (1st March 1998) - J, Sebastiäo; Formosinho,; Arnaut, Luis; Fausto, Rui
The microscopic descriptions of electron transfer (ET) reactions given by Marcus theory (MT) and by the intersecting-state model (ISM) are compared with ab initio calculations on O2/O2. and C6H6/C6H6. model systems. The activated configuration calculated by ab initio methods agrees only with that of ISM. Solvent effects in self-exchange rates and in intervalence bands of mixed-valence symmetrical compounds are shown to be smaller than predicted by dielectric continuum models. MT and ISM are used to calculate self-exchange and cross-reaction rates of transition-metal complexes and organic species. It is shown that a compensation of effects may take place in MT calculations. Absolute ET rate calculations using ISM are in good agreement with experiment when non-adiabatic factors are included in σ*(d) electron exchanges. It is shown that ISM reproduces different types of free-energy profiles (Rehm-Weller behaviour, Marcus inverted region, double inverted region) with only one adjustable parameter. The donor-acceptor distance dependence, temperature dependence and free-energy dependence of intramolecular ET reactions are calculated with two adjustable parameters. These calculations are within an order of magnitude of the experimental rates.